2016
DOI: 10.1111/aos.13227
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation in an animal model of acute ocular hypertension

Abstract: PurposeTo analyse miRNA regulation in a rat model of acute ocular hypertension (AOH).MethodsAcute ocular hypertension (AOH) was induced in the left eye of adult albino rats by inserting a cannula connected with a saline container into the anterior chamber. The contralateral eye served as a control. Seven days later, animals were killed. Retinas were used either for quantitative analysis of retinal ganglion cells (RGCs) and microglial cells or for miRNA array hybridization, qRT‐PCR and Western blotting.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…While abundance of particular BMSC-miRNA in comparison to fibroblasts is critical for the identification of candidates, sEV-mediated delivery of miRNA to the retina can only be effective if the packaged miRNA are not already abundantly present in the injured retina. For example, one recent study analyzed rat retina 7 days after ocular hypertension, 49 using microarray to detect overabundant miRNA, whereas a separate study analyzed 16 human retina from cadavers without any retinal pathology, determining the 40 most highly abundant. 50 From these studies and the identified miRNA of the present study; MIR-144-5P , MIR-126-5P , and MIR-100-5P were found to also be overabundant in BMSC sEV.…”
Section: Discussionmentioning
confidence: 99%
“…While abundance of particular BMSC-miRNA in comparison to fibroblasts is critical for the identification of candidates, sEV-mediated delivery of miRNA to the retina can only be effective if the packaged miRNA are not already abundantly present in the injured retina. For example, one recent study analyzed rat retina 7 days after ocular hypertension, 49 using microarray to detect overabundant miRNA, whereas a separate study analyzed 16 human retina from cadavers without any retinal pathology, determining the 40 most highly abundant. 50 From these studies and the identified miRNA of the present study; MIR-144-5P , MIR-126-5P , and MIR-100-5P were found to also be overabundant in BMSC sEV.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has already been described in detail previously. 23,52 In anesthetized rats, a 30-gauge infusion needle connected to a 500-ml bottle of sterile saline was placed into the anterior chamber of the left eye, taking care not to injure the lens or iris, and this did not cause alteration of the basal IOP levels. Elevation of the saline bottle above the level of the eye to a height of 150 mm above the rat resulted in an IOP elevation to 76 6 3 mm Hg, which was maintained for a period of 75 minutes ( Fig.…”
Section: Induction Of Aohmentioning
confidence: 99%
“…22 Another experimental model to study glaucoma consists of inducing an acute ocular hypertension (AOH), a situation that may mimic acute angle-closure glaucoma but may also result in retinal ischemia and lead to ON damage and RGC loss. 23 Adult rodent RGCs comprise many subtypes, each one with its own typical functional, morphologic, and projecting attributes, and this makes it challenging to characterize the iovs.arvojournals.org j ISSN: 1552-5783 response of particular RGC types to experimental retinal insults. 24 For the rat retina there are only two molecular markers that can make a clear distinction between the general population of RGCs, implied in image-forming functions, that are labeled with Brn3a antibodies and the intrinsically photosensitive RGCs, implied in nonimage forming functions, which can be largely identified with melanopsin antibodies (m þ RGCs).…”
mentioning
confidence: 99%
“…On the other hand, more and more evidence has demonstrated that retinal complications of diabetes are the result of functional and structural alterations in both the microvascular and neuroglial compartments, and DR is widely recognized to be a neuro‐vascular disease . In our previous study, in the acute high intraocular pressure rat model, miR‐93‐5p was also significantly decreased, which suggested that the miRNA is involved in the apoptosis and inflammation of the retina . Furthermore, we also found that miR‐93‐5p could regulate the activation of retinal microglia through the signal transducer and activator of transcription 3 (STAT3) pathway (preliminary data).…”
Section: Discussionmentioning
confidence: 63%
“…41,42 In our previous study, in the acute high intraocular pressure rat model, miR-93-5p was also significantly decreased, which suggested that the miRNA is involved in the apoptosis and inflammation of the retina. 43 Furthermore, we also found that miR-93-5p could regulate the activation of retinal microglia through the signal transducer and activator of transcription 3 (STAT3) pathway (preliminary data). Therefore, miR-93-5p may also be involved in the pathogenesis of PDR through regulating the apoptosis and inflammation of retina cells.…”
Section: Discussionmentioning
confidence: 78%